2011
DOI: 10.1149/2.057202jes
|View full text |Cite
|
Sign up to set email alerts
|

In Situ STM Study of Cu Electrodeposition on TBPS-Modified Au(111) Electrodes

Abstract: The impact of 3,3'-thiobis(1-propanesulfonic acid, sodium salt) (TBPS) on Cu/Au(111) electrodeposition has been investigated by electrochemical methods and scanning tunneling microscopy (STM). Cyclic voltammetry and galvanostatic experiments indicate that Cu growth on Au(111) - which is known to be strongly kinetically hindered in additive-free, aqueous perchloric acid solutions - proceeds significantly faster in the presence of TBPS. The TBPS molecules either "float" on top of the growing film or be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…21,25,38,[57][58][59][60] STM studies have confirmed that the thioether group (i.e., the C-S−C bond) of TBPS does not chemically cleave but that TBPS still can form a SAM on an Au(111) surface after TBPS is adsorbed onto the Au(111) surface, even facilitating copper deposition on the Au(111) surface. 45,46 This result implies that the thioether group of TBPS can chemically adsorb onto gold and copper surfaces, similar to the thiol group of MPS and the disulfide group of SPS; however, it also implies that the adsorptive bonding strength between the thioether group and copper is weaker than the adsorptive bonding strength of Cu-thiolate. Therefore, its accelerating effect on copper electrodeposition is weaker than the effects of SPS and MPS, as confirmed by the CV analysis shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…21,25,38,[57][58][59][60] STM studies have confirmed that the thioether group (i.e., the C-S−C bond) of TBPS does not chemically cleave but that TBPS still can form a SAM on an Au(111) surface after TBPS is adsorbed onto the Au(111) surface, even facilitating copper deposition on the Au(111) surface. 45,46 This result implies that the thioether group of TBPS can chemically adsorb onto gold and copper surfaces, similar to the thiol group of MPS and the disulfide group of SPS; however, it also implies that the adsorptive bonding strength between the thioether group and copper is weaker than the adsorptive bonding strength of Cu-thiolate. Therefore, its accelerating effect on copper electrodeposition is weaker than the effects of SPS and MPS, as confirmed by the CV analysis shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…31,38 TBPS is a new additive that is able to accelerate copper electrodeposition. 45,46 However, an effective plating formula for copper superfilling using TBPS as an accelerator has not yet been developed. Figure 2 shows the CV curves of these organosulfide-modified Au electrodes in an electrolyte containing 0.88 M CuSO 4 , 0.54 M H 2 SO 4 , 200 ppm PEG, and 70 ppm Cl − .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations